2017
DOI: 10.1055/s-0037-1607195
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Microscopic Transsphenoidal Surgery of Craniopharyngiomas: A Systematic Review of Surgical Outcomes Over Two Decades

Abstract: Both techniques appear comparable for infradiaphragmatic lesions; however, TE seems to yield better results for supradiaphragmatic tumors. In conclusion, more complex lesions with difficult locations can be effectively treated with endoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
1
5
1
Order By: Relevance
“…In the stratified analysis, the EEA did not show any significant difference in the adult (OR = 1.84, 95% CI 0.41-8.16, p = 0.424) and mixed (OR = 2.45, 95% CI 0.87-6.87, p = 0.066) groups for achieving a higher GTR rate as compared with TCA. Generally, although a higher GTR rate was commonly considered as an advantage of the EEA by most published researchers, the results from our study and those of several recent studies did not support this superiority, suggesting that the possibility of the surgical technique of the TCA in neurosurgeons might have improved along with the development of other surgical techniques [11,40]. Moreover, Younus et al confirmed that the higher GTR rate was significantly achieved by senior specialists than surgeons with limited clinical practice (71% vs. 47%, p < 0.05), suggesting that the GTR rate in EEA might increase as neurosurgeons improve their surgical process using the EEA in the next decade [41].…”
Section: Publication Biascontrasting
confidence: 94%
“…In the stratified analysis, the EEA did not show any significant difference in the adult (OR = 1.84, 95% CI 0.41-8.16, p = 0.424) and mixed (OR = 2.45, 95% CI 0.87-6.87, p = 0.066) groups for achieving a higher GTR rate as compared with TCA. Generally, although a higher GTR rate was commonly considered as an advantage of the EEA by most published researchers, the results from our study and those of several recent studies did not support this superiority, suggesting that the possibility of the surgical technique of the TCA in neurosurgeons might have improved along with the development of other surgical techniques [11,40]. Moreover, Younus et al confirmed that the higher GTR rate was significantly achieved by senior specialists than surgeons with limited clinical practice (71% vs. 47%, p < 0.05), suggesting that the GTR rate in EEA might increase as neurosurgeons improve their surgical process using the EEA in the next decade [41].…”
Section: Publication Biascontrasting
confidence: 94%
“…27 A recent meta-analysis found 67.8% GTR and 21% recurrence for endoscopic endonasal CP resections. 5 However, irregular and jagged tumor borders, often large size, and adhesion to nearby structures make surgery particularly difficult, making safe GTR impossible. 28 Postoperative visual deterioration ranges between 0% and 33%.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Gross total resection (GTR) significantly reduces recurrence; however, recently, several centers have opted for subtotal resection followed by adjuvant RT to reduce postoperative sequelae. 4-9 Conventional RT has been the primary treatment for residual/recurrent CPs for decades, but it can cause collateral hypothalamic, pituitary, and ocular damage, especially in young patients. Stereotactic radiosurgery (SRS) permits precise irradiation, thus minimizing unnecessary radiation exposure; however, large volume and neighboring organ at risks (OARs) limit single-fraction SRS.…”
mentioning
confidence: 99%
“…Hydrocephalus was among the least frequent complications for both surgical approaches; some authors were more concerned about hydrocephalus as a pre-existing condition than a surgical complication [ 44 ]. However, Cagnazzo et al presented results suggesting hydrocephalus was more common after the transsphenoidal endoscopic procedure [ 45 ]. Komotar et al also showed that EEA carried a higher incidence for this complication, at 15.80% compared to 10.10% for TCA.…”
Section: Discussionmentioning
confidence: 99%